Мeasurement of rotational temperature of molecular nitrogen in the anode area of negative corona in air under Тrichel pulse mode - Bolotov, O.V.; Golota, V.I.; Sitnikova, Yu.V. (Вопросы атомной науки и техники, 2018)
Experimental results of investigations of emission spectra of the second positive system of molecular nitrogen
from the anode area of negative corona discharge in air are presented. In the Trichel pulse mode, the radiation intensity distribution in the electronic-vibrational-rotational С³
Пu(0)-В₃Пg(0) transitions of molecular nitrogen is analyzed. Based on the analysis of the rotational structure of the spectral lines, taking into account the Boltzmann distribution of the rotational levels population, the rotational temperature (~ 470 K) of the molecular nitrogen in the
anode area is determined. A theoretical calculation of emission spectra of the R-branch rotational lines is carried out Наведено результати експериментальних досліджень спектрів випромінювання другої позитивної системи молекулярного азоту з прианодної області негативної корони в повітрі в режимі імпульсів Тричела. Проаналізовано розподіл інтенсивності випромінювання в електронно-коливально-обертальних переходах
С³ Пu(0)-В₃Пg(0) молекулярного азоту. На основі аналізу обертальної структури спектральних ліній, з урахуванням больцманівського розподілу заселеності обертальних рівнів, визначена обертальна температура молекул азоту (~470 K) у прианодній області розряду. Проведено теоретичний розрахунок спектрів випромінювання обертальних ліній R-гілки обертальної структури спектра. Приведены результаты экспериментальных исследований спектров излучения второй положительной системы молекулярного азота из прианодной области отрицательной короны в воздухе в режиме импульсов
Тричела. Проанализировано распределение интенсивности излучения в электронно-колебательновращательных переходах С³ Пu(0)-В₃Пg(0) молекулярного азота. На основе анализа вращательной структуры
спектральных линий, с учетом больцмановского распределения заселенности вращательных уровней, определена вращательная температура молекул азота (~470 K) в прианодной области разряда. Проведен теоретический расчет спектров излучения вращательных линий R-ветви вращательной структуры спектра.